PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 030 UJUNG TANJUNG KECAMATAN TANAH PUTIH - Marhadi, Hendri; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The use of cooperative learning model of Group Investigation (GI) helps the process of learning mathematics in SDN 030 Ujung Tanjung. This study aims to improve learning outcomes mathematics Elementary School fourth grade SDN 030 Ujung Tanjung Tanah Putih by implementing cooperative learning model of Group Investigation (GI). This research is a classroom action research. In this study used two research instruments namely learning devices and data collection instruments. Based on the results of research and discussion that has been described, the following: Activity of teachers in the application of cooperative models Group Investigation (GI) in the first cycle of the first meeting increased 55.55%, 66.66% the second meeting, the first meeting of the second cycle 68.88% increase the second meeting be 88.88%. Activities of students in the application of cooperative models Group Investigation (GI) obtain data on the first cycle of the first meeting increased 52.77% and 63.88% second meeting, then at the first meeting of the second cycle obtain increased 88.88% 69.44% The second was a meeting. Learning outcomes of students has increased an average start preliminary data obtained with an average of 61.56 or (43.75%) students who completed 7 of 16 students. After improvement of learning through cooperative model of type Group Investigation (GI), the UH first cycle increased by an average gained 70.94 or (62.50%) students who completed 10 of 16 students. UH increased in the second cycle with an average of 83.12 or (81.25%) students who completed 13 of 16 students. Key Words: Cooperative Learning Model of Group Investigation (GI), Math Learning Outcomes